Analisis Pengaruh Variasi Massa Material Arang Terhadap Proses Desalinasi Air Laut Tenaga Surya - Ojan, Alfond Fasselis; Tarigan, Ben V.; Adoe, Dominggus G. H. (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2022)
Desalination is the process of distilling seawater using a heat source from solar energy to obtain fresh water. Therefore, one of the methods used to increase the results of the seawater desalination process is to make a tool using solar energy and charcoal material. This research was conducted to determine the effect of using charcoal material on the seawater desalination process. The use of charcoal material is expected to increase the absorption of heat energy and accelerate the evaporation process of seawater. In this study, the highest efficiency was obtained in basin I with a mass of 500 grams of charcoal, namely 5.393% with 70 ml of water produced, followed by basin IV without using charcoal material with an efficiency of 6.116% with fresh water produced of 60 ml, followed by basin IV. II with a mass of 400 grams of charcoal obtained an efficiency of 1.585% with 59 ml of water produced. And in basin III the efficiency and fresh water produced is less, namely 0.004% and the water produced is 41 ml